Rethinking Hidradenitis Suppurativa Management: Insights into Bacterial Interactions and Treatment Evolution - Faith D. Huynh; Giovanni Damiani; Christopher G. Bunick (Antibiotics, 2024)
Hidradenitis suppurativa (HS), or acne inversa, is a chronic inflammatory dermatological condition characterized by painful and recurrent nodules and purulent abscesses. HS can have a devastating impact on the quality of life of patients. This condition is commonly localized to the axilla, groin, perineal, and inframammary regions, and can develop fistulas and sinus tracts over time. Its pathogenesis remains elusive and is best characterized at the moment as multi-factorial. Additionally, questions remain about the role of cutaneous dysbiosis as a primary HS trigger or as a secondary perturbation due to HS inflammation. This article features works in relation to HS and its interplay with bacterial microflora. We address current treatment approaches and their impact on HS-related bacteria, as well as areas of therapeutic innovation. In the future, disease-modifying or remittive therapy will likely combine an advanced/targeted anti-inflammatory approach with one that effectively modulates cutaneous and deep tissue dysbiosis.